2022
DOI: 10.30762/jeels.v8i1.3058
|View full text |Cite
|
Sign up to set email alerts
|

Face-To-Face Or Online Speaking Practice: A Comparison of Students’ Foreign Language Classroom Anxiety Level

Abstract: Speaking using foreign language in front of other people can be one of the most anxiety-provoking situations (Minghe & Yuan, 2013). Learners who does not enjoy interacting with other people or being the center of attention may exhibit extreme anxiety when they are asked to take parts in oral presentation, discussion, or any other kind of language activities. A study found that online discussion may decrease the effect. It provides a non-threatening situation for learners who are shy and withdrawn (Bakar et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The second mechanism is that in a virtual environment, players are represented by avatars, which can create a sense of anonymity that can increase enjoyment of the experience [ 63 ]. Furthermore, learners in a traditional face-to-face learning environment have reported that they may feel self-conscious about speaking up in front of others, fearing judgment or criticism [ 64 ]. Based on Chen and Kent [ 65 ], one reason can be that the anonymity provided through avatars can create a sense of security that can shield learners from feeling embarrassed or singled out when making mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism is that in a virtual environment, players are represented by avatars, which can create a sense of anonymity that can increase enjoyment of the experience [ 63 ]. Furthermore, learners in a traditional face-to-face learning environment have reported that they may feel self-conscious about speaking up in front of others, fearing judgment or criticism [ 64 ]. Based on Chen and Kent [ 65 ], one reason can be that the anonymity provided through avatars can create a sense of security that can shield learners from feeling embarrassed or singled out when making mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism is that in a virtual environment, players are represented by avatars, which can create a sense of anonymity that can increase enjoyment of the experience (58). Furthermore, learners in a traditional face-to-face learning environment have reported that they may feel self-conscious about speaking up in front of others, fearing judgment or criticism (59). Based on Chen and Kent (60), one reason can be that the anonymity provided through avatars can create a sense of security that can shield learners from feeling embarrassed or singled out when making mistakes.…”
Section: Potential Mechanisms Behind the Ndingsmentioning
confidence: 99%
“…Interaksi sosial juga dapat meningkatkan rasa percaya diri siswa dalam berkomunikasi dalam bahasa target. Ketika siswa merasa nyaman berbicara dan berinteraksi dengan teman sekelas dalam bahasa Korea, mereka cenderung lebih berani dalam menggunakan bahasa tersebut di berbagai situasi (Omar et al, 2020;Yaniafari & Rihardini, 2021). Rasa percaya diri ini merupakan faktor penting dalam pengembangan keterampilan berbahasa yang baik.…”
Section: Interaksi Sosialunclassified